2020
DOI: 10.21203/rs.3.rs-58150/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional response of Bacillus megaterium FDU301 to PEG200-mediated arid stress

Abstract: Background: For microorganisms on a paper surface, the lack of water is one of the most important stress factors. A strain of Bacillus megaterium FDU301 was isolated from plaques on a paper surface using culture medium with polyethylene glycol 200 (PEG200) to simulate an arid condition. Global transcriptomic analysis of B. megaterium FDU301 grown under normal and simulated arid conditions was performed via RNA-seq technology to identify genes involved in arid stress adaptation.Results: The transcriptome of B. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Aerobic metabolism also generates endogenous oxidative stress if O2 is not completely reduced during respiration and a secondary oxydative stress response can also be triggered when Bacillus encounter unfavorable conditions in an aerobic environment [47]. All these stresses are counteracted by the action of proteins such as catalases (Kat), superoxide dismutases (SodA) or DNA-binding ferroxidases (Dps) [48, 49], all of which are overexpressed in 7 dpi bacteria. RNA-Seq analysis also revealed that the BTB_c10430 locus, annotated as encoding the SigX protein [26], is specifically up-regulated in 7 dpi bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic metabolism also generates endogenous oxidative stress if O2 is not completely reduced during respiration and a secondary oxydative stress response can also be triggered when Bacillus encounter unfavorable conditions in an aerobic environment [47]. All these stresses are counteracted by the action of proteins such as catalases (Kat), superoxide dismutases (SodA) or DNA-binding ferroxidases (Dps) [48, 49], all of which are overexpressed in 7 dpi bacteria. RNA-Seq analysis also revealed that the BTB_c10430 locus, annotated as encoding the SigX protein [26], is specifically up-regulated in 7 dpi bacteria.…”
Section: Discussionmentioning
confidence: 99%